Assessment of the Challenges of Public Provision of Potable Water in Emohua Local Government Area, Rivers State, Nigeria - Wocha Chikagbum (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
Water is required for the existence of both plant and animal. Its importance cannot be overemphasized, no wonder the United Nations declared access to safe, clean drinking water and sanitation a fundamental human right, according to the declaration, right to water is essential for life, upholding dignity, and key to actualization of Sustainable Development Goal (SDG) 6-which aims at ensuring availability and sustainable management of water and sanitation for all by 2030. The problem of public provision of potable water supply in Nigeria is a recurring decimal and in recent times, the issue of the public water supply has remained silent in the governance lexis. In Rivers State the water corporation (water board) has the responsibility of providing water for the public but failed in this responsibility due to a number of reasons such as monitoring and evaluation, funding and financing, increasing population growth, poor institutional framework corruption etcetera. The study adopted a cross-sectional survey research design with the use of a multi stage research, purposive sampling and simple ramdon method. Fifteen (15) communities were listed and 4 communities- Ibaa, Rumuji, Ndele and Obele-Ibaa were purposively selected. 200 heads of households were selected using simple random sampling while 50 respondents were allocated to each community on the basis of the population to ensure equal representation. Primary data were collected using closed ended structured and multiple response questionnaires. Secondary data were obtained from relevant policy documents and published literature and data analyzed using descriptive statistics, including frequencies and percentages, and results were presented in tables. The study revealed that there is a complete dependence on private water sources in all the four communities, indicating that there is no operational public water supply. Again, Institutional failures are the primary impediments to public water provision. High prevalence of water-related diseases with seventy-five percent of households reporting at least one case of water-related illness. Respondents prioritized proper planning, increased investment, infrastructural development and close monitoring as measures that can be taken to ensure public water provision. The study concluded that the Lack of public water supply in Emohua LGA is a problem of governance which is driven by corruption, weak planning, and poor maintenance of facilities and that the high level of community willingness to pay and partner with government offers a good opportunity to leverage on for the resurgence of public water sector in the study area. The key recommendations were establishment of independent monitoring mechanism, increase in the investment on water infrastructure, transparent project implementation, and revamping dilapidated water facilities in other locations that may adversely impact on the study area.